Study of Antioxidant Properties and Influence on Mitochondrial Bioenergetics of a Composition Consisting of Mono Ammonium Salt of Glycyrrhizic Acid and Amino Acids - Dalimova, Surayyo; Tukhtaev, Davron; Muhammadjonova, Guzal; Dadakhonova, Mukhlisa; Yunusova, Muslima; Khamdamova, Nigora; Seit-Asan, Lenara (Journal of Neonatal Surgery, 2025)
The antioxidant effect and influence of a composition consisting of monoammonium salt of glycyrrhizic acid (MASGA) and amino acids - cysteine, methionine, and tryptophan on the bioenergetics of rat liver mitochondria in paracetamol-induced liver damage in rats were studied. It has been established that paracetamol causes a significant increase in the liver homogenate of diene conjugates and conjugated trienes, as well as a secondary product of lipid peroxidation (LPO) - malondialdehyde (MDA). In the liver mitochondria, under the influence of paracetamol, there is a decrease in respiration and oxidative phosphorylation processes. The introduction of the studied composition to hepatitis animals reduced the content of primary and secondary LPO products and partially restored the functional state of the mitochondria.